2005
DOI: 10.2139/ssrn.832626
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and Triggers: Situational Mechanics of Gender in Negotiation

Abstract: The authors propose two categories of situational moderators of gender in negotiation: situational ambiguity and gender triggers. Reducing the degree of situational ambiguity constrains the influence of gender on negotiation. Gender triggers prompt divergent behavioral responses as a function of gender. Field and lab studies (1 and 2) demonstrate that decreased ambiguity in the economic structure of a negotiation (structural ambiguity) reduces gender effects on negotiation performance. Study 3 shows representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
174
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(193 citation statements)
references
References 78 publications
(20 reference statements)
15
174
1
3
Order By: Relevance
“…14 Social psychological research has shown that women tend to ask for and negotiate less money than men when the parameters for asking are unclear. 15 From an institutional perspective, there is evidence that women receive less administrative and technical support than men in the sciences [16][17][18][19] and less professional support from senior mentors or colleagues. 5 Other work suggests that the progress of women in academic medicine remains taxed by sex-based biases and stereotypes that favor men.…”
Section: Discussionmentioning
confidence: 99%
“…14 Social psychological research has shown that women tend to ask for and negotiate less money than men when the parameters for asking are unclear. 15 From an institutional perspective, there is evidence that women receive less administrative and technical support than men in the sciences [16][17][18][19] and less professional support from senior mentors or colleagues. 5 Other work suggests that the progress of women in academic medicine remains taxed by sex-based biases and stereotypes that favor men.…”
Section: Discussionmentioning
confidence: 99%
“…There is a vast literature on economic experiments (not related to corruption) that revealed gender differences in behavior, for instance during negotiations (Bowles et al, 2005), in competitive environments (Gneezy et al, 2003), related to the provision of public goods and altruism (Andersen et al, 2008), or to the expectation one might have with respect to the behavior of men or women (Aguiar et al, 2009), to name a few. A recent overview on the literature on gender differences in economic experiments can be found in Croson and Gneezy (2009).…”
Section: Introduction: Exploring the Gender-corruption Nexusmentioning
confidence: 99%
“…Studies that have examined the effects of situational factors on negotiating performance of men and women (Kray et al, 2002;Watson, 1994) have suggested that differences in negotiated outcomes are more a function of the context than gender. More recent work by Bowles et al (2005) concluded that performance was a function of the interaction of the negotiation context and individual differences of the negotiator. Kray et al's (2002) study focused on the effects of stereotype threat (Steele, 1997), Watson (1994) examined the impact of power differentials, and Bowles et al (2005) examined contextual ambiguity.…”
mentioning
confidence: 99%